Human Resources Management as a Catalyst for SME Competitiveness - Muhammad Ramdhan; Muhamad Ridwan (AKTIVA: Journal of Accountancy and Management, 2026)
Research Purpose: This study aims to examine the role of Human Resource Management (HRM) in enhancing the competitiveness of Small and Medium Enterprises (SMEs) in Cianjur by exploring how HRM practices contribute to employee performance and business sustainability in rural SMEs.Method or Approach: This study employed a qualitative research design using semi-structured interviews, observations, and documentation involving SME owners, managers, and employees. Data were analyzed descriptively to identify HRM practices and their influence on organizational competitiveness.Research Findings: The findings reveal that HRM practices in SMEs are predominantly informal and integrated into daily operational activities. Recruitment is mainly based on personal relationships, while employee development occurs through on-the-job learning. Performance management relies on direct supervision and verbal feedback, whereas motivation is supported by flexible working arrangements and informal incentives. These practices positively affect employee productivity, adaptability, and work quality. SME competitiveness is reflected in customer retention, product innovation, and market expansion through digital platforms.Recommendations and Novelty: The study highlights that effective informal HRM practices can strengthen SME competitiveness. The novelty lies in its contextual analysis of adaptive and sustainable HRM strategies in rural SMEs within the digital era. Tujuan: Penelitian ini bertujuan untuk mengkaji peran Manajemen Sumber Daya Manusia (MSDM) dalam meningkatkan daya saing Usaha Mikro, Kecil, dan Menengah (UMKM) di Cianjur dengan menelaah kontribusi praktik MSDM terhadap kinerja karyawan dan keberlanjutan usaha pada UMKM pedesaan. Metode: Penelitian ini menggunakan desain penelitian kualitatif melalui wawancara semi-terstruktur, observasi, dan dokumentasi yang melibatkan pemilik, manajer, dan karyawan UMKM. Data dianalisis secara deskriptif untuk mengidentifikasi praktik MSDM dan pengaruhnya terhadap daya saing organisasi. Hasil Penelitian: Hasil penelitian menunjukkan bahwa praktik MSDM pada UMKM masih bersifat informal dan terintegrasi dalam aktivitas operasional sehari-hari. Rekrutmen dilakukan berdasarkan hubungan personal, sedangkan pengembangan karyawan dilakukan melalui pembelajaran langsung di tempat kerja. Manajemen kinerja diterapkan melalui pengawasan langsung dan umpan balik verbal, sementara motivasi kerja didukung oleh fleksibilitas kerja dan insentif informal. Praktik tersebut berkontribusi terhadap produktivitas, kemampuan adaptasi, dan kualitas kerja karyawan. Daya saing UMKM tercermin dari loyalitas pelanggan, inovasi produk, dan perluasan pasar melalui platform digital.Rekomendasi dan Kebaruan: Penelitian ini menunjukkan bahwa praktik MSDM informal yang efektif mampu memperkuat daya saing UMKM. Kebaruan penelitian terletak pada analisis kontekstual mengenai strategi MSDM yang adaptif dan berkelanjutan pada UMKM pedesaan di era digital.